Studi Blending Nikel Antara Barging Stockpile Dengan Hasil Aktual Pada PT Ariano Bintang Cemerlang: Study Of Nickel Blending Between Barging Stockpile and Actual Yield at PT Ariano Bintang Cemerlang - Bakri, Suriyanto; Gaffar, Abd; Juradi, Muhammad Idris (Journal of Engineering Science and Technology Applications, 2023)
PT Ariano Bintang Cemerlang, Kolaka, Southeast Sulawesi, is one of the companies that manages laterite nickel ore into ferronickel (FeNi) products, with a Cut Off Grade (COG) of 1.40% Ni. In the nickel management process, one of the important steps taken is blending. However, in practice, differences are often found between the projected nickel quality of the barging stockpile and the actual results after the blending process. This study aims to analyze the correspondence between the nickel quality at the barging stockpile and the actual results after blending, identify the factors that affect the difference, and provide recommendations for optimizing the blending process. This study uses a quantitative approach to analyze the conformity between the nickel quality at the barging stockpile and the actual results after the blending process. The results of the blending process analysis show that actual blending has a tendency to produce higher elemental levels in some parameters compared to plan blending. The difference between plan blending and actual blending data can be caused by the material in the stockpile, the inaccuracy of material retrieval, the efficiency of the blending equipment and process, the moisture content and condition of the material, the method of analysis and sampling. A more structured management of materials in the stockpile is needed to minimize these differences.